Characteristics of Hypertension Patients in the Working Area of the Parlilitan District Health Center, Humbang Hasundutan Regency, North Sumatra Province, 2023 - Manahan Tua Tinambunan; Mardiati Barus; Ance Siallagan (Jurnal Kesehatan, Rekam Medis dan Farmasi (JUK-Medifa), 2025)
Hypertension is an increase in blood flow that occurs in the human body and is a leading cause of death globally. Hypertension does not only affect the elderly but also individuals of productive age. It is also referred to as the “silent killer.” This study aims to describe the characteristics of hypertension patients in the working area of the Upt Health Center, Parlilitan District, Humbahas Regency, North Sumatra Province, in 2023. This study used a descriptive method. The sampling technique employed was total sampling, with a total of 86 respondents. The measurement tool used was an Observation Sheet. The results showed that respondents aged 55–65 years numbered 30 (34.9%), while those aged 26–35 years numbered 4 (4.7%). Based on gender, 46 respondents were male (53.5%) and 40 were female (46.5%). Based on education, 33 respondents (38.4%) had completed senior high school/vocational school, and 14 respondents (16.3%) had attended higher education. Based on occupation, 43 respondents (50.0%) were farmers, 12 (14.0%) were housewives, and 31 (36.2%) were civil servants. Regarding marital status, 84 respondents (97.7%) were married, while 2 respondents (2.3%) were unmarried. Regarding medication, 67 respondents (66.3%) did not consume hypertension medication, while 34 respondents (33.7%) did. Based on symptoms frequently experienced by respondents, 71 respondents (82.6%) reported dizziness, and 15 respondents (17.4%) reported pain. Based on the study results, most hypertension patients had blood pressure classified as hypertension grade II, totaling 40 respondents (50.5%), while the minority were in the prehypertension category, totaling 8 respondents (7.9%).